Towards a Textual Deconstruction of Adebowale’s Lonely Days - Wolé Olúgúnlè (Journal of Language and Literature, 2021)
No literary creation exists hermetically; it is not self-sufficient and independent. It does not emanate from a vacuum. Every literary creation is textually incorporated in relation; whether compulsorily, optionally or accidentally, to other pre-existing texts. This implies that the realization of a literary text by a writer results from the fact that such literary creator has studied several other pre-existing texts; thus it is presumptuous of a writer to claim the competence of producing a literary text without dialoging with existing ideas and ideologies, mœurs, legends and myths as well as pre-existing communication codes. But then, the objective of this study is to unearth and demonstrate how Adebowale, in his Lonely Days (2006), has related in either a compulsory, optional or accidental manner with existing ideas and ideologies, mœurs, legends and myths and pre-existing communication codes. With Kristevan methodology of intertextuality and critical textual analysis, the study succinctly deconstructs how the textual incorporation of the hypertext relates with the existing hypo-texts through the markers of intertextuality. The study finds out that, in its consistent relationship with other pre-existing texts, the text is stylistically incorporated in with the view to reconstructing and revalorizing the African altered history and culture while portraying the reality of women’s condition in male African hegemonic societies. It concludes that the realization of any literary text and preoccupation is relational to existing texts.